Chemical composition and healing potential of essential oil of Dennettia tripetala on methicillin-resistant Staphylococcus aureus: infected wound model (2022)
Background: Dennettia tripetala (Pepperfruit) is an important medicinal plant in some West African communities. This study was designed to examine thè antibacterial properties and wound-healing abilities of D. tripetala essential oil on mice with methicillin-resistant Staphylococcus aureus (MRSA) infections. Gas chromatography-mass spectrom- etry (GC-MS) was used to analyse thè essential oil (EO) extracted by hydro-distillation from thè dried fruits of D. tripetala. MRSA was identified using 30 pg cefoxitin disk, CHROMagar, and Polymerase Chain Reaction. Congo red agar and tube technique were used toassessthe production of biofìlms.The antimicrobial susceptibilityfor both antibiot- ics and essential oil was determined by Kirby Bauer and broth dilution methods. Eleven male mice were used in thè in vivo study, and each animai had wound infection on thè dorsal inter-scapular skin region created with a 6 mm biopsy punch and 50 pi (adjusted to 0.5 McFarland standard) of MRSA. The size ofthe wound and its histological characteris- tics were used to estimate healing rate. Results: The GC-MS investigation ofthe essential oil revealed six compounds, with benzene (2-nitroethyl) being thè most prominent. Out ofthe eighteen (18) isolates examined, 12 MRSA strains were identified using thè three methods for methicillin resistance determination, with about 80% of them being classified as biofilm producers. More than 60% ofthe MRSA isolates were resistant to erythromycin, fusidic acid, gentamicin and trimethoprim/sulfamethoxazole. The essential oil had greater antibacterial activity than thè reference antibiotic, vancomycin.The essential oil had a minimum inhibitory concentration of80 l/ml and a minimum bactericidal concentration of 160 l/ml (v/v). Haema- toxylin and eosin staining revealed that thè skin tissue that had been exposed to D. tripetala essential oil had a thicker epithelial layer, numerousfibroblasts, a build-up of collagen, and many blood cells. Condusions: The results showed that D. tripetala essential oil has powerful anti-staphylococcal properties as well as thè capacity to expedite wound healing.This suggests that D. tripetala essential oil could be a successful candidate for developing a topical agent for wound management.